Enhancing Consumer Loyalty through Product Quality and Word of Mouth in MSME's - Istanti, Fredianaika; Maftukhah, Ida; Azizah, Zainab; Kusuma, Nadia Ingrida (Universitas Negeri Semarang, 2025)
MSMEs contribute to labor absorption and drive local economic growth. This study aims to analyze the role of product quality and word of mouth on consumer loyalty through consumer satisfaction as an intervening variable among MSME product users in Semarang City. This research is motivated by the important role of MSMEs in employment and their contribution to driving local economic growth. Therefore, understanding the factors influencing consumer loyalty is crucial for maintaining the sustainability of MSME businesses. The approach used in this study is quantitative with an explanatory research method. Data analysis was conducted using SEM (Structural Equation Modeling) based on PLS (Partial Least Squares) to examine the relationships between the variables studied. The study population was MSME product users in Semarang City. The sampling technique used was purposive sampling with 200 respondents. Data collection was conducted through questionnaires. The results show that product quality has a positive and significant effect on consumer loyalty. Word of mouth has a positive and significant effect on consumer loyalty. Consumer satisfaction has a positive and significant effect on consumer loyalty. Product quality has a positive and significant effect on consumer satisfaction. Word of mouth has a positive and significant effect on consumer satisfaction. Furthermore, customer satisfaction has been shown to mediate the influence of product quality and word of mouth on customer loyalty. The implications of this research indicate that improving product quality and optimizing word of mouth, both directly and through increased customer satisfaction, can be an effective strategy for MSMEs to build and maintain customer loyalty in Semarang City. These findings are expected to provide a basis for MSMEs and policymakers to design programs to improve product quality and strengthen word-of-mouth promotion in a more targeted manner.